Yes 11.6 is a greater than 11.3
I hope that's help !
Answer:
103 and 68
Step-by-step explanation:
Given
A + B = 171
A - B = 35
Add the two expressions to eliminate B.
B + (-B) = B - B = 0
We have
2A = 206
Divide both sides by 2 to isolate A
2A/2 = 206/2
A = 103
Now substitute 103 for A in either expression to get B
Using the first expression , we have
A + B = 171
103 + B = 171
Subtract 103 from both sides
103 - 103 + B = 171 - 103
B = 68
The numbers are 103 and 68
Check
103 + 68 = 171
103 - 68 = 35
Answer:
103 and 68
Step-by-step explanation:
since the difference has to be 35 subtract 35 from 171 (equals 136) then divide it by 2, you get 68 which is your first number, then add 35 back and get 103 for the second number, I hope this helped
Answer:
Step-by-step explanation:
Distribute 2(x+2):
2(x) + 2(2) = 2x + 2
Use the FOIL method to multiply (2x + 2)(x+6)
(2x + 2)(x+6)
2x(x) = 2
2x(6) = 12x
2(x) = 2x
2(6) = 12
2 + 12x + 2x + 12 = 2 + 14x + 12
Graph the following equation on a graphing calculator, and then you should know how to graph it on paper.
PLEASE HELP!
WILL GIVE BRAINLIEST FOR FASTEST CORRECT ANSWER!
50 POINTS!
Answer:
-12x - 42.
Step-by-step explanation:
-6 * 2x - 6 * 7
Now, multiply -6 by 2x and -6 by 7:
-12x - 42
So, the simplified expression is -12x - 42.
Answer: -12x - 42
Step-by-step explanation:
First, -6(2x) is -12x then -6(7) is -42
That makes -12x - 42